Sarcopenia in adults with congenital heart disease: Nutritional status, dietary intake, and resistance training. Issue 1 (July 2019) - Shiina, Yumi; Matsumoto, Noriko; Okamura, Daisuke; Takahashi, Yuta; Kijima, Yasufumi; Fukuda, Terunobu; Kawamatsu, Naoto; Nishihata, Yosuke; Komiyama, Nobuyuki; Niwa, Koichiro
Highlights: Skeletal muscle mass index was lower in adults with congenital heart disease (CHD), suggesting sarcopenia. Calorie, protein, and fat intake in adults with CHD was higher than controls. Resistance training and amino acid intake increased skeletal muscle in adults with CHD. Resistance training and amino acid intake also improved edema index, and N-terminal prohormone of brain natriuretic peptide levels. Appropriate nutritional education and resistance training guidelines should be provided. Abstract: Background: This study aimed (1) to assess the nutritional status and dietary intake, (2) compare the body composition and nutritional intake between sarcopenia and non-sarcopenia, and (3) evaluate the effects of resistance training and amino acid intake in adults with congenital heart disease (CHD). Methods: Study 1 In total, 172 adults with CHD were prospectively enrolled. The Food Frequency Questionnaire was used, and body composition analysis was conducted.Study 2 : Thirty of 172 adult patients with CHD were divided into two groups: amino acid intake plus resistance training (group A) and amino acid intake only (group B) for 2 months. Results: Study 1: Skeletal muscle mass index was lower in adults with CHD compared to healthy Japanese. Calorie, protein, and fat intake in adults with CHD was higher than those in the National Nutritive Intake Investigation; however, the difference in carbohydrate or salt intake was non-significant.Study 2 : In adults with CHD in group A, body fat percentage, edema index, and N-terminal prohormone of brain natriuretic peptide improved, and body weight, skeletal muscle mass index, and basic metabolism increased after the intervention. There was no improvement after intervention for group B. Conclusions: According to this study, adults with CHD have higher calorie, protein, and fat intake than those in a national survey despite decreased skeletal muscle mass. Amino acid intake plus resistance training positively improved body fat percentage, skeletal muscle mass, and edema in adults with CHD. Appropriate nutritional education and resistance training guidelines should be provided.